Influence of ferrite nanoparticle type and content on the crystallization kinetics and electroactive phase nucleation of poly(vinilidene fluoride) - Sencadas, Vítor João Gomes Silva (2011)
This work reports on the nucleation of the β-phase of poly(vinylidene fluoride), PVDF, by incorporating CoFe2O4 and NiFe2O4 nanoparticles, leading in this way, to the preparation of magnetoelectric composites. The fraction of filler nanoparticles needed to produce the same β- to α-phase ratio in crystallized PVDF is one order of magnitude lower in the Cobalt nanoparticles. The interaction between nanoparticles and PVDF chains induce the all trans conformation in PVDF segments and this structure then propagates in crystal growth. The nucleation kinetics is enhanced by the presence of nanoparticles, as corroborated by the increasing number of spherulites with increasing nanoparticle content and by the variations of the Avrami’s exponent. Further, the decrease of the crystalline fraction of PVDF with increasing nanoparticles content indicates that an important fraction of polymer chains are confined in interphases with the filler particle.